Provision of Gefitinib as Targeted Therapy in Lung Adenocarcinoma with EGFR Mutation and Brain Metastatic - Widiasari, Komang Sri Rahayu (Malang Respiratory Journal, 2019)
Adenocarcinoma is a malignant epithelial tumor with glandular differentiation or mucin production. Adenocarcinoma covers 30% of lung cancers in Europe and America. This report described a case of an unusual chronic headache since 3 years ago without any complementing symptom except for nausea. The primary tumor was detected with Thorax CT scan and confirmed by histopathology examination. Patient treated with gefitinib (1 x 250 mg) and showed a satisfying result. Gefitinib, as first-line therapy for patients with epidermal growth factor receptor ( EGFR) mutation, was effective and well-tolerated in this patient.